Exploring the Anticancer Potential of Premna resinosa (Hochst.) Leaf Surface Extract: Discovering New Diterpenes as Heat Shock Protein 70 (Hsp70) Binding Agents - Valentina Parisi; Giuliana Donadio; Maria Laura Bellone; Soumia Belaabed; Ammar Bader; Angela Bisio; Valeria Iobbi; Erica Gazzillo; Maria Giovanna Chini; Giuseppe Bifulco; Immacolata Faraone; Antonio Vassallo (Plants, 2023)
Premna, a genus consisting of approximately 200 species, predominantly thrives in tropical and subtropical areas. Many of these species have been utilized in ethnopharmacology for diverse medicinal applications. In Saudi Arabia, Premna resinosa (Hochst.) Schauer (Lamiaceae) grows wildly, and its slightly viscid leaves are attributed to the production of leaf accession. In this study, we aimed to extract the surface accession from fresh leaves using dichloromethane to evaluate the anticancer potential. The plant exudate yielded two previously unknown labdane diterpenes, Premnaresone A and B, in addition to three already described congeners and four known flavonoids. The isolation process was accomplished using a combination of silica gel column chromatography and semi-preparative HPLC, the structures of which were identified by NMR and HRESIMS analyses and a comparison with the literature data of associated compounds. Furthermore, we employed a density functional theory (DFT)/NMR approach to suggest the relative configuration of different compounds. Consequently, we investigated the possibility of developing new chaperone inhibitors by subjecting diterpenes 1–5 to a Surface Plasmon Resonance-screening, based on the knowledge that oridonin, a diterpene, interacts with Heat Shock Protein 70 (Hsp70) 1A in cancer cells. Additionally, we studied the anti-proliferative activity of compounds 1–5 on human Jurkat (human T-cell lymphoma) and HeLa (epithelial carcinoma) cell lines, where diterpene 3 exhibited activity in Jurkat cell lines after 48 h, with an IC50 of 15.21 ± 1.0 µM. Molecular docking and dynamic simulations revealed a robust interaction between compound 3 and Hsp70 key residues.